Scanning electron microscopy assessment of the load-bearing capacity of cad/cam-fabricated molar crowns - Emine Göncü BAŞARAN; Güliz AKTAŞ; Pekka VALLITTU; Lippo LASSILA; Mehmet Cudi TUNCER (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Although fiber-reinforced composites are commonly used in dental practice, whether fiber-reinforced crowns and fixed partial dentures can be used as definitive prostheses remains to be determined. This study used scanning electron microscopy to evaluate the load-bearing capacity of non-reinforced and fiber-reinforced composite (FRC) molar crowns prepared by computer-aided design/computer-aided manufacturing (CAD/CAM). The crowns were fabricated from three empirical FRC blocks, one empirical composite block, and one commercial ceramic block. The FRC resin was prepared by mixing BaO silicate particles, E-glass fiber, and dimethacrylate resin. Specimens were divided into five groups (n = 10), differing in the amounts of filler, resin, and fiber. Crowns were statically loaded until fracture. One-way analysis of variance and Tukey's post hoc multiple comparison tests were used for statistical analyses. The groups showed significant differences in load-bearing capacity; empirical bidirectional FRC resin blocks had the highest capacity, while commercial ceramic blocks had the lowest capacity. Molar crowns formed from FRC resin blocks had higher load-bearing capacity compared to non-reinforced composite resin and ceramic blocks. These results show that fiber reinforcement increased the load-bearing capacity of molar crowns.